Hypothermic Oxygenated Perfusion Improves Extended Criteria Donor Liver Graft Function and Reduces Duration of Hospitalization Without Extra Cost: The PERPHO Study. Issue 3 (12th March 2021) - Rayar, Michel; Beaurepaire, Jean‐Marie; Bajeux, Emma; Hamonic, Stéphanie; Renard, Thomas; Locher, Clara; Desfourneaux, Véronique; Merdrignac, Aude; Bergeat, Damien; Lakehal, Mohamed; Sulpice, Laurent; Houssel‐Debry, Pauline; et al.
Abstract : Few studies have evaluated the efficacy or the cost of hypothermic oxygenated perfusion (HOPE) in the conservation of extended criteria donor (ECD) grafts from donation after brain death (DBD) donors during liver transplantation (LT). We performed a prospective, monocentric study (NCT03376074) designed to evaluate the interest of HOPE for ECD‐DBD grafts. For comparison, a control group was selected after propensity score matching among patients who received transplants between 2010 and 2017. Between February and November 2018, the HOPE procedure was used in 25 LTs. Immediately after LT, the median aspartate aminotransferase (AST) level was significantly lower in the HOPE group (724UI versus 1284UI; P = 0.046) as were the alanine aminotransferase (ALT; 392UI versus 720UI; P = 0.01), lactate (2.2 versus 2.7; P = 0.01) There was a significant reduction in intensive care unit stay (3 versus 5 days; P = 0.01) and hospitalization (15 versus 20 days; P = 0.01). The incidence of early allograft dysfunction (EAD; 28% versus 42%; P = 0.22) was similar . A level of AST or ALT in perfusate >800UI was found to be highly predictive of EAD occurrence (areas under the curve, 0.92 and 0.91, respectively). The 12‐month graft (88% versus 89.5%; P = 1.00) and patient survival rates (91% versus 91.3%; P = 1.00) were similar. The additional cost of HOPE was estimated at € 5298 per patient. The difference between costs and revenues, from the hospital's perspective, was not different between the HOPE and control groups (respectively, € 3023 versus € 4059]; IC, –€ 5470 and € 8652). HOPE may improve ECD graft function and reduce hospitalization stay without extra cost. These results must be confirmed in a randomized trial. Abstract : https://www.wileyhealthlearning.com/Activity2/7277075/Activity.aspx?parentActivityId=0